PRODUKSI BIOGAS DARI SAMPAH BUAH DAN SAYUR: PENGARUH VOLATILE SOLID DAN LIMONEN - , Piyantina Rukmini ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Biogas is one of alternative enegy resources that is being developed and renewable. Utilization of fruit and vegetable wastes are done to convert organic material to be energy. The raw materials that used is rotten orange (Citrus sinensis Osbeck) and cabbage (Brassica oleracea). Rotten orange content carbohydrates that can be made to biogas, but it has limonene. Limonene can inhibit the gowth of the bacteria in the methanogenesis phase in anaerobic digester. This research aims to know the influence of volatile solid and limonene to biogas production from fruit and vegetable waste. This research uses 6 unit of erlenmeyers 500 mL, waterbath, water manometer, and thermometer. Total volume of the digester is 350 mL. Adjusment of the pH in the start up is done to make the optimum condition for pH growth ofmethanogen ( 6,8 - 7,8). Toxicity of oksigen can be healed by spraying N2 in the digester in the beginning. Research is done under mesophilic conditions (30-40oC), during 50 days. The data is collected based on analysis before and during the degradation process. . The results show that the digester that has same VS (Tl and T3 with 15% VS, T2 and T4 with 20%VS) with different concentration of rotten orange /limonene (Tl = 114ppm < T3= 170ppm, and T2= 152ppm < T4= 225ppm), hence digester with higher concentration of orang peel/limonen will produce higher acetic acid every week. Accumulation of acetic acid in acidogenesis phase because of the limonene cause the methanogen bacteria cannot growth in the next phase (methanogenesis). At the same conditions, the volume of biogas that has higher concentration of rotten orange /limonene (Tl <T3, and T2<T4) will produce higher accumulation ofbiogas volume (Tl= 54.963 cm3< 1'3= 46.372 cm3, T2= 60.314 cm3< T4= 69.191 cm3). At concentration of rotten orange /limonene 114 ppm, will obtain 0.1298 %V/grVS of methane concentration.